The creation of spinoff companies by academic inventors: An important entrepreneurial phenomenon to catalize economic development - Malik, Javed Nayyar; Mahmood, Rosli (2011)
The spin-off companies established by academic inventors are an important entrepreneurial phenomenon as well as a vital catalyst for economic development. Thereupon, this paper will bring clarity to understand the process involved by which university spinoffs emerged; specifically the intentions, motivations of university-based inventors and the factors influencing actual spinoff activities such as to form companies and otherwise commercialize inventions in universities.